Development of Ethnomathematics-Based Modules Assisted by the Canva Application to Improve Understanding of Scientific Literacy and Mathematical of Pirie-Kieren Theory - Farid Imroatus Sholihah; Salma Zahranaya Fatikha; M. Haviz; Rian Vebrianto (Jurnal Penelitian Pendidikan IPA, 2026)
This research is motivated by the limited ethnomathematics learning tools that specifically explore local culture and the lack of analysis of students' scientific literacy and mathematical understanding based on Pirie-Kieren's theory. This study aims to develop an ethnomathematics module based on Tulungagung's traditional batik that is valid, practical, and effective in improving students' scientific literacy and mathematical understanding. Using the Research and Development (R&D) method with the 4D model (Define, Design, Develop, and Disseminate), this study involved 60 ninth-grade students as trial subjects. The research instruments included a validation questionnaire, observation sheets, and an understanding test. The results of the material expert validation showed a percentage of 88.31%, and the teacher practitioner validation was 88.65%, both of which are in the valid category. The small group trial resulted in a score of 81.53% (very good). In the field test, the experimental class used a module assisted by the Canva application, while the control class used conventional teaching materials. The analysis results showed that students in the experimental class were able to achieve eight layers of thinking according to Pirie-Kieren's theory, while the control class only achieved five layers. Thus, the Tulungagung batik ethnomathematics module is proven to meet the quality criteria and has a significant effect on improving students' scientific literacy and mathematical understanding comprehensively.